PROBING THE ALIGNMENT BETWEEN MULTIMODAL TEACHING PRACTICE AND STUDENTS’ LEARNING PREFERENCES IN INDONESIAN EFL CLASSROOM - Novia Trisanti; Henrikus Joko Yulianto; Daud Jiwandono; Almira Irwaniyanti Utami (University of Kuningan, 2026)
In Indonesia, teaching and learning English are confronted with various obstacles in aligning instructional approaches with students’ learning preferences and multimodal literacy expected by the curriculum. Multimodal pedagogy has been widely promoted in EFL contexts. However, few research have studied the alignment between teachers’ multimodal teaching approaches and students’ preferred learning modalities in authentic classrooms. This research explored the perceived alignment of multimodal teaching with student’s learning preferences in the Indonesian secondary EFL classroom. A mixed-method approach was employed in this study with 20 EFL teachers and 60 junior high school students in Semarang Regency, Indonesia. Data were obtained by Likert scale questionnaire and open-ended response and analyzed by descriptive statistics and qualitative analysis. The results showed that students had the highest preference for kinesthetic learning (M = 7.78) and video-based media (70%), while the lowest preference was for audio-based learning (M = 3.04). Students had generally good perception of teachers’ use of multimodal media. However, the convergence of instructional practices to students’ chosen modalities was only partial as indicated by the moderate mean scores ranging from 3.45 to 3.58. The qualitative data findings to support the quantitative analysis results also reflect that the students preferred interactive and visually aided learning activities since they raised engagement and understanding. This study reveals multimodal pedagogy has been applied in Indonesian EFL classrooms, although further pedagogical adaptation and teacher support are needed to meet learner diversity and maximize multimodal instruction.